Correlation of Taxpayer Awareness, Rase of Payment, and Quality of Service with Taxpayer Compliance PKB (Pajak Kendaraan Bermotor) in SAMSAT Office, Klaten District - Erna Chotidjah Suhatmi; Agus Suyatno; Retna Dewi Lestari (Proceeding of International Conference on Science, Health, And Technology, 2021)
This study examines the correlation between tax awareness, ease of payment, and service quality with taxpayer compliance to pay Pajak Kendaraan Bermotor (PKB). The data in this study is the type of ordinal data using a Likert scale. The validity and reliability of the questions asked in the Likert scale questionnaire have been tested using the bivariate correlation test. The sample of this research is 75 taxpayers who are registered in the taxpayers UPPD (Unit Pengelola Pendapatan Daerah) Klaten District or the Samsat Office of Klaten District in 2021. The sampling technique uses simple random sampling technique, which is to determine a sample of taxpayers randomly. Analysis of the data used to determine the relationship between taxpayer awareness, ease of payment, and service quality with tax compliance is by using the Spearman Rank Correlation. The results of this study indicate that three questions on tax awareness, four questions on the ease of paying taxes, and four questions on the quality of tax services are valid and realiable. The validity and reality test shows that the question or item has a valid and consistent bivariate and Cronbach Alpha correlation value. The results of the Spearman Rank correlation between tax awareness and paying compliance produce a correlation value of 0.730, which means that the correlation between the two variables is strong. Meanwhile, the result of the correlation between the ease of paying taxes and compliance in paying taxes results in a value of 0.557, which means that is strong. The relationship between the quality of tax services at the Samsat Office of Klaten District with paying compliance results in a correlation value of 0.479 which means the relationship is sufficient. So it can be concluded that taxpayer awareness and ease of payment have a strong correlation with taxpayer compliance to pay Pajak Kendaraan Bermotor (PKB) in Samsat Office of Klaten District.